First-line chemotherapy for mCRC—a review and evidence-based algorithm - Cremolini, Chiara; Schirripa, Marta; Antoniotti, Carlotta; Moretto, Roberto; Salvatore, Lisa; Masi, Gianluca; Falcone, Alfredo; Loupakis, Fotios (Nature reviews. Clinical oncology, 2015)
Response to first-line therapy is a primary determinant of outcome in patients with metastatic colorectal cancer (mCRC). In the past decade, the development of antiangiogenic and anti-EGFR biologic agents, doublet and triplet chemotherapy regimens, and combinations of these treatment modalities has created not only new first-line treatment options, but also new challenges for the management of this disease. In this Perspectives, these advances and the confusion surrounding their implications are discussed. The authors attempt to address some of the challenges in clinical decision-making and propose an algorithm for personalized allocation of first-line treatments in patients with mCRC. The response to first-line therapy is a primary determinant of outcome in patients with metastatic colorectal cancer (mCRC), for three main reasons: effective upfront therapy provides a unique opportunity to cure some patients; can be crucial in delaying disease progression and achieving symptom relief; and can improve patient eligibility for, and the effectiveness of, further treatments. In the past decade, decision-making regarding the choice of first-line therapy for mCRC has been complicated by the availability of many different options without a definitive consensus on a specific standard of care (despite major advances in categorizing predictive molecular disease subtypes). Most of the efforts of the scientific community have been directed at establishing the best biologic agent to be combined with a chemotherapy doublet, although a different branch of research has produced new data that underscore the importance of defining the optimal chemotherapy backbone. Herein, we review the key clinical trials completed in the past 10 years that have investigated and compared the use of chemotherapy doublets, triplets, and monotherapies, with or without molecularly targeted biologic agents, in the first-line treatment of patients with mCRC. Our examination of the literature led us to propose a new patient-oriented algorithm to guide clinicians' decisions on the best choice of upfront therapy for mCRC.